E-Learning, E-Education, and Online Training : second International Conference, eLEOT 2015, Novedrate, Italy, September 16-18, 2015, revised selected papers /: second International Conference, eLEOT 2015, Novedrate, Italy, September 16-18, 2015, revised selected papers. (2016) - Unknown
No abstract available